Microenvironmental features drive the distribution of lichens in the House of the Ancient Hunt, Pompeii, Italy. (January 2019) - Tonon, C.; Favero-Longo, S.E.; Matteucci, E.; Piervittori, R.; Croveri, P.; Appolonia, L.; Meirano, V.; Serino, M.; Elia, D.
Abstract: On the stone cultural heritage, the influence of architecture-related microenvironmental features on lichen diversity, abundance and consequent threats for conservation has been still poorly characterized to support management plans. Such relationships were here investigated on the vertical surfaces of the House of the Ancient Hunt in Pompeii, archaeological site in S-Italy where the variability of lichen saxicolous communities has been still completely neglected despite their widespread occurrence. Lichen colonization in semiconfined rooms was sporadic and limited to Dirina massiliensis, while a remarkable turnover of six communities, encompassing 22 species, characterized mortar, painted and plastered surfaces in outdoor environments, with local covers up to 80%. Microscopic and spectroscopic analyses displayed the deteriogenic potential of three dominant species, due to hyphal penetration within paint and plaster layers ( Verrucaria macrostoma ) and the release of oxalic acid and/or secondary metabolites with acidic and chelating functions ( D. massiliensis, Lepraria lobificans ). A higher vertical distance of surfaces from the ground and a larger room dimension were the main conditional factors related to a higher lichen abundance and the distribution of the different communities. Such knowledge on architecture-related microenvironmental features driving lichen distribution and biodeterioration threats may contribute to address restoration priorities and conservation strategies. Highlights: Lichens are remarkable biodeteriogens in the Pompeii archaeological area. Different species display different physical and/or chemical deteriogenic potential. Species turnover is detected between and within the rooms of a Pompeian house. Architecture-related environmental features drive distribution of lichen communities. Knowledge on driving factors of lichen distribution addresses restoration priorities.